KARAKTERISTIK WARNA IKAN ASIN SEPAT SEBAGAI INDIKATOR PENGAWET FORMALIN DI PASAR TRADISIONAL DESA TUNAS JAYA MUARADUA - Syariani BR Tambunan; Nico Syahputra; Nurdin Amin (Universitas Islam Negeri Ar-Raniry, 2017)
The danger of formalin may cause respiratory tract irritation, vomiting, dizziness, burning in the throat, liver damage, heart, brain, kidney and central nervous system. However, salted fish marketed is still found to contain formalin. The research covers the field of food and beverage chemistry which aims to describe formalin in salted fish sold in the Traditional Market of Tunas Jaya Village Muaradua. Of all fish populations of spicy fish all were sampled using purposive sampling technique based on texture and color. While the method used is Color Test. From the research of qualitative formalin on the salted fish of Sepat fish, it is known that from 30 samples of salted fish which in the society is expected to be more careful in choosing the salted fish sepat to be consumed not only based on the color and texture, but it does not contain formalin. The conclusion of this research is Formalin on Salted Fish Sepat that sold in Traditional Market of Desa Tunas Jaya Muaradua Year 2012 positively containing formalin equal to 60% in society.